Research on extracting and preparing a Puerariae Flos and Chrysanthemum-based drink - Chunmei Quan
In traditional Chinese medicine, Puerariae Flos and Chrysanthemum are widely utilized in herbal teas for hangover relief and heat-clearing detoxification. In this study, a new drink has been developed, employing these two flowers as primary raw materials. The objective of this study was to optimize the optimal formula, extraction process, and preparation method for the drink. The optimization of the formula and extraction process was guided by the utilization of the total flavonoids content in the water decoction of the two flowers as an indicator. Based on the sensory evaluation criteria, including color, smell, taste, and state of the drink, the water decoction addition, honey addition, and citric acid addition were optimized by single-factor experiments and orthogonal experiments. The best formula and extraction process was 10 g of Puerariae Flos, 10 g of Chrysanthemum, 48 min of decocting time, and 615 mL of water. The optimal preparation process consisted of 30% water decoction, 8% honey, and 0.025% citric acid. Subsequently, a golden yellow, transparent, and stable liquid was produced, possessing a sweet taste along with the distinctive aroma and flavor of Puerariae Flos and Chrysanthemum.